2016
DOI: 10.15171/jcvtr.2016.08
|View full text |Cite
|
Sign up to set email alerts
|

Isolated parachute mitral valve in a 29 years old female; a case report

Abstract: A 29-year old female patient was referred to our hospital for evaluation of dyspnea NYHA class I which begun from several months ago. The only abnormal sign found on physical examination was a grade 2/6 systolic murmur at the apex position without radiation. Echocardiography revealed normal left and right ventricular sizes and systolic function, and only one papillary muscle in left ventricular (LV) cavity which all chordae tendineae inserted into that muscle. The mitral valve orifice was eccentrically located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…7 an isolated case of adult parachute mitral valve in a 29 year old female was reported in 2016 but none of those had severe mitral stenosis leading to severe pulmonary arterial hypertension. 8 Incidence rate has been estimated at 0.6% of necropsy cases of congenital heart disease and 0.21% to 0.42% of clinical case. 9 Mean age at first hospitalization for cardiac disease was 2.1 years (range birth to 9.5 years) but it was not until a mean age of 4.5 years (range 21 days to 13 years) that the definitive diagnosis of congenital mitral stenosis was established.…”
Section: Discussionmentioning
confidence: 99%
“…7 an isolated case of adult parachute mitral valve in a 29 year old female was reported in 2016 but none of those had severe mitral stenosis leading to severe pulmonary arterial hypertension. 8 Incidence rate has been estimated at 0.6% of necropsy cases of congenital heart disease and 0.21% to 0.42% of clinical case. 9 Mean age at first hospitalization for cardiac disease was 2.1 years (range birth to 9.5 years) but it was not until a mean age of 4.5 years (range 21 days to 13 years) that the definitive diagnosis of congenital mitral stenosis was established.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review by Hakim et al, only 9 adult patients with PMV have been described till 2010 [6]. As in our case, an isolated case of PMV in a twenty-nineyear-old woman was described in 2016 [9]. In 2018 Bade et al reported 2 cases of severe inborn mitral stenosis associated with severe pulmonary hypertension secondary to PMV [10].…”
Section: Discussionmentioning
confidence: 46%
“…[ 3 ] The outcomes of patients with a parachute mitral valve are dependent on the spectrum of associated cardiac lesions, with the degree of mitral valve obstruction remaining stable; the majority will not require valvotomy. [ 4 ] Surgical treatment consists of either choral fenestration or papillary muscle splitting, with or without commissurotomy. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%